Speculative machines and technical mentalities: a philosophical approach to designing the future. Issue 2 (2nd April 2016) - Brassett, Jamie
Abstract: 'Beyond their instrumental functions', writes Rivka Oxman in an article about design, creativity and innovation (2013), 'advanced digital and computational environments are also becoming tools for thinking design'. At the leading edge of creativity and innovation design does not only speculate the plausible, possible or potential, but pragmatically inserts such futures into the present (as Whitehead says any 'immediate existence' (1962) must). Using concepts mainly from Deleuze, Guattari, Spinoza and Simondon, I will position such design speculation as pragmatic, divergent, complex and emergent. That is, as manifesting the technical mentalities (Simondon) that provide the milieu in which we can show what we 'might be capable of' (Stengers).